Can the 'single point of entry' strategy be used to recapitalize a failing bank? - Peter J. Wallison; Paul H. Kupiec (American Enterprise Institute (AEI), 2014)
We analyze the ability of the "Single Point of Entry" strategy (SPOE) to resolve large banks without financial market disruption. We identify several legal and financial impediments that could prevent SPOE's use. In particular, Title II of the Dodd-Frank Act was conceived by Congress as an alternative to bankruptcy liquidation, not a mechanism for recapitalizing financial institutions through SPOE or otherwise, especially banks. The failure of the largest banks will not generally endanger the solvency of parent BHCs, preventing the secretary of the Treasury from using SPOE for these major institutions. However, other large BHCs would be bankrupt if their subsidiary bank failed, and here SPOE expands the government safety net and reinforces TBTF. On balance, the evidence suggests that SPOE does not solve TBTF or provide a way to recapitalize a failing bank.
Keywords: A; 330; Dodd-Frank Act; banking